2015
DOI: 10.1155/2015/406096
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Preimplantation Genetic Diagnosis for Hemophilia at the University Hospital Virgen Del Rocío in Spain: Technical and Clinical Overview

Abstract: Hemophilia A and B are the most common hereditary hemorrhagic disorders, with an X-linked mode of inheritance. Reproductive options for the families affected with hemophilia, aiming at the prevention of the birth of children with severe coagulation disorders, include preimplantation genetic diagnosis (PGD). Here we present the results of our PGD Program applied to hemophilia, at the Department of Genetics, Reproduction and Fetal Medicine of the University Hospital Virgen del Rocío in Seville. A total of 34 cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Compared with a previously reported hexaplex panel where two out of four extragenic markers are >1 Mb from the F8 gene , all extragenic markers in our panel locate within 0.6 Mb from the F8 gene, thus minimizing misdiagnosis or no diagnosis caused by recombination between the markers and the F8 gene. Using this newly developed panel, the percentage of individuals harboring at least one heterozygous intragenic marker (~80%) and one heterozygous extragenic marker on each side of the F8 gene (~98%) was higher compared with another hexaplex panel (~70% and ~86%, respectively) in the Chinese population .…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Compared with a previously reported hexaplex panel where two out of four extragenic markers are >1 Mb from the F8 gene , all extragenic markers in our panel locate within 0.6 Mb from the F8 gene, thus minimizing misdiagnosis or no diagnosis caused by recombination between the markers and the F8 gene. Using this newly developed panel, the percentage of individuals harboring at least one heterozygous intragenic marker (~80%) and one heterozygous extragenic marker on each side of the F8 gene (~98%) was higher compared with another hexaplex panel (~70% and ~86%, respectively) in the Chinese population .…”
Section: Discussionmentioning
confidence: 76%
“…Therefore, this new panel improves the odds of identifying markers that are informative for use in standalone indirect linkage analysis, or as a complement to direct mutation detection, in couples wishing to undergo PGD for HEMA. Several reports have demonstrated that multiplex marker PCR is a reliable indirect linkage-based PGD method for cases involving inversion mutations [19][20][21][22]. Hence, this tetradecaplex marker panel, which contains more markers than previously reported panels, is likely to benefit carriers of the intron-1 or intron-22-mediated inversion mutations the most, because direct single-cell mutation detection is not possible and indirect linkage analysis is the only option [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Most patients with HB can be detected by direct DNA sequencing. Moreover, we noticed that some clinics still offered PGD for HB families by gender selection, and transfer of only female embryos 13 and few researches about PGD of HB has been reported. 9 Preimplantation genetic diagnosis cycle which is an advanced assisted conception technique that gives couples the chance of giving birth to an unaffected child of a specific disease is regarded as a better option since possible termination of an affected pregnancy after prenatal diagnosis frequently confronts to the religious, ethics, and culture.…”
Section: Introductionmentioning
confidence: 99%
“…Success rates of around 30% have been reported. 31 Carriers of male fetuses confirmed to be affected by severe haemophilia should be counselled to enable informed choices. 32 Evidence level 4…”
mentioning
confidence: 99%